Rhetoric in debt - Sharp-Hoskins, Kellie, 1982- (RSA series in transdisciplinary rhetoric., 2023)
"Examines the relationship between rhetoric and debt, arguing that they are fundamentally entangled in producing and disciplining who is deemed worthy of credit and how debt materializes differentially: as a credit to some and condemnation of others"--